2023
DOI: 10.1073/pnas.2302534120
|View full text |Cite
|
Sign up to set email alerts
|

Antisense oligonucleotide rescue of CGG expansion–dependent FMR1 mis-splicing in fragile X syndrome restores FMRP

Abstract: Aberrant alternative splicing of mRNAs results in dysregulated gene expression in multiple neurological disorders. Here, we show that hundreds of mRNAs are incorrectly expressed and spliced in white blood cells and brain tissues of individuals with fragile X syndrome (FXS). Surprisingly, the FMR1 (Fragile X Messenger Ribonucleoprotein 1) gene is transcribed in >70% of the FXS tissues. In all FMR1 -expressing FXS tissues, FMR1 RNA itself… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Gene expression and RNA splicing are mis-regulated in the Fmr1 -deficient mouse hippocampus [ 15 ] and FXS patient-derived blood samples [ 26 ]. To determine whether this mis-regulation occurs in other brain regions and in peripheral tissues from mice, we sequenced RNA from ( n = 3, 2- to 3-month-old) WT and Fmr1 KO hippocampus, cerebellum, and cortex, as well as liver, muscle, and testis ( Fig 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Gene expression and RNA splicing are mis-regulated in the Fmr1 -deficient mouse hippocampus [ 15 ] and FXS patient-derived blood samples [ 26 ]. To determine whether this mis-regulation occurs in other brain regions and in peripheral tissues from mice, we sequenced RNA from ( n = 3, 2- to 3-month-old) WT and Fmr1 KO hippocampus, cerebellum, and cortex, as well as liver, muscle, and testis ( Fig 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…A number of strategies have been developed to reduce the symptoms of FXS through pharmacology (Davenport et al, 2016; Yamasue et al, 2019), reactivating FMRP expression (Xie et al, 2016; Graef et al, 2019; Yrigollen and Davidson, 2019; Shah et al, 2023), or inducing FMRP expression through delivery of viral constructs (Zeier et al, 2009; Gholizadeh et al, 2014; Hampson et al, 2019; Wong et al, 2023). An early study attempted to reintroduce the full length FMRP conjugated to tat as a cell permeable protein, but reported toxicity when tested in fibroblasts (Reis et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A number of strategies have been developed to reduce the symptoms of FXS through pharmacology (Yamasue et al, 2019), reactivating FMRP expression (Xie et al, 2016;Graef et al, 2019;Yrigollen and Davidson, 2019;Shah et al, 2023), or inducing FMRP expression through delivery of viral constructs (Hampson et al, 2019). It was recently found that reintroducing the N-terminus of FMRP as a tat conjugate peptide achieved rapid transport across the BBB, rescuing circuit functions and alleviating symptoms of Fmr1 KO mice (Zhan et al, 2020).…”
Section: Rescue Of Fmrp Function In Fxsmentioning
confidence: 99%
“…(CAG)n NRE in huntingtin (HTT) exon 1 caused aberrant splicing and pre-mature cleavage and polyadenylation in both knock-in mouse models of HD and patient tissues 48 , resulting in truncated yet still translatable mRNAs for polyQ synthesis. In addition to transcriptional silencing, mis-splicing of FMR1 mRNAs in individuals with fragile X syndrome further reduces FMRP abundance 49 . Furthermore, multiple intronic NREs have been shown to suppress canonical splicing and to cause the retention of their respective host introns 50,51 , including (CCTG)n in CNBP intron 1 (DM2), (CTG)n in TCF4 intron 3 (Fuchs endothelial corneal dystrophy), and (GGCCTG)n. in NOP56 intron 1 (SCA36).…”
Section: Discussionmentioning
confidence: 99%